Never say sell how the world's best consulting and professional services firms expand client relationships - McMakin, Tom; Parks, Jacob (John Wiley & Sons, Inc., 2021)
"Key rainmakers at firms like McKinsey, IBM, and Deloitte report that 80 percent of their new revenues come from existing clients, not from new logos. Never Say Sell is a how-to guide for executives, account teams, and sole proprietors for growing exiting accounts and turning their one-and-done clients into a source of recurring revenue. Most providers will explain account growth by saying, "Do good work," arguing if they deliver value to clients, then clients will want more of their expertise and turn to them again and again for help. Unfortunately, this truism is as unhelpful as it is wrong. Never Say Sell reveals the truth and describes a new client-centered approach to account development"--
Includes bibliographical references and index. - Online resource; title from digital title page (viewed on December 29, 2020)
Keywords: Relationship marketing; Customer relations; Consulting firms -- Marketing; Customer services -- Marketing; Marketing relationnel; Customer services; Marketing